Changes in the multi‐scale structure and physicochemical properties of starch during potato growth. (19th April 2021) - Yang, Liping; Liu, Yong; Yang, Jianting; Du, Chuanlai; Zhai, Ligong
Abstract: BACKGROUND: Growth stage contributes critically to the physicochemical properties of starches, which make achieving desired functional properties by controlling the growth period possible. Thus, this study investigated the changes in multiscale structure and physicochemical properties of potatoes starches harvested at different growth stages. RESULTS: The amylose and phosphate content varied over the growth period, with the ranges 2.756–2.998 g kg −1 and 0.0058–0.0077 g kg −1, respectively. The starch granules were round or oval, and the size increased with growth. X‐Ray diffraction indicated the B‐type crystalline structure of samples. Time‐dependent changes in crystallinity were observed. The weight‐average molecular weight ( M w ) showed a tendency to decrease first and then increase, and presented the lowest M w (1.105 × 10 8  g mol −1 ) at 35 days. A higher proportion of long chains were noted in starch from earlier harvested potatoes than that in later harvested ones. Differential scanning calorimetry revealed that starch gelatinization temperature decreased, and gelatinization enthalpy decreased from 16.39 to 14.89 J g −1 . All samples possessed weak elastic gel‐like structure, and starches harvested at early stage possessed highest viscosity and stronger gel behaviour. Resistant starch showed a decreasing trend on the whole, and presented highest value (10.69%) at earliest harvest time. Starch from the potatoes harvested at 35 days after tuberization exhibited excellent light transmittance (up to 62.47%). CONCLUSION: Potato starches harvested at different growth period presented extremely different structures and physicochemical properties. The results will provide fundamental data in terms of changes of potato starch during growth which will affect the choice of harvest time. © 2021 Society of Chemical Industry.